Geopolymer bricks prepared by MSWI fly ash and other solid wastes: Moulding pressure and curing method optimisation. (November 2022) - Bai, Yanying; Guo, Weichao; Wang, Jianwei; Xu, Zehua; Wang, Shuai; Zhao, Qingxin; Zhou, Jinman
Abstract: The preparation of geopolymer from alkaline solid waste instead of strong alkali presents the disadvantage of low early strength. However, improving the early mechanical properties of the geopolymer to meet the engineering requirements is challenging. In this paper, the effects of different moulding pressures and curing methods on the properties of red mud–ground granulated blast furnace slag activated by municipal solid waste incineration fly ash (MSWIFA)–carbide slag (CRMG) were studied and evaluated in terms of compressive strength and XRD, FTIR, SEM, and MIP techniques analysis. The results showed that the moulding pressure of 30 MPa could increase the compressive strength at 3 d by 182% and decrease the porosity from 30.28% to 27.38%. These results are attributable to the fact that the moulding pressure causes the particles to be tightly bound and promotes the geopolymerisation reaction. High-temperature (HT) curing could accelerate the hydration reaction and increase the compressive strength at 3 d by 133.7% and 141.6% compared with those obtained by water curing (WC) and room-temperature (RT) curing, respectively. Microscopic analyses showed that HT curing can promote the generation of C–(A)–S–H gel, geopolymer gel and hydrate calcium chloroaluminate (HCC), fill the pores, and increase the structure's compactness. Finally, the proposed method was verified by synthesising geopolymer pavement bricks (GPB), and the compressive strength at 3 d was found to reach 54 MPa under an optimal curing method (moulding pressure of 30 MPa, 90 °C for 12 h). Compared with concrete pavement bricks, GPB presents broad application prospects for saving economic costs and protecting the environment. The results provide a theoretical basis and technical support for the application of CRMG in rapid demoulding projects such as unfired bricks. Graphical abstract: Image 1 Highlights: CRMG can be applied to rapid demoulding engineerings, such as pavement bricks. Moulding pressure reduces the total pore volume, but increases the macropore volume. HT curing promotes the occurrence of hydration reaction and crack propagation. Moulding pressure and HT curing can effectively improve the early strength.